Genital ulcer disease in men in Durban, South Africa. Issue 4 (August 1991) - O'Farrell, N; Hoosen, A A; Coetzee, K D; van den Ende, J
Abstract : OBJECTIVE--To study the microbial aetiology of genital ulcer disease (GUD) in men. DESIGN--Microbiological and clinical assessment of genital ulcers in men. SETTING--City Health sexually transmitted diseases clinic, King Edward VIII Hospital, Durban, South Africa. PARTICIPANTS--100 Zulu men with genital ulcers who had not received antibiotics in the previous four weeks. RESULTS--Syphilis was diagnosed in 42%, chancroid in 22%, donovanosis (granuloma inguinale) in 11%, genital herpes in 10% and lymphogranuloma venereum (LGV) in 6%. No pathogens were identified in 24%. Mixed infections were detected in 14 men, in whom 13 had syphilis. Five men had HIV-1 antibodies. Neisseria gonorrhoeae was isolated from the ulcers and urethra in seven men and from the urethra alone in five. Scabies was diagnosed clinically in eight. CONCLUSIONS--All the major causes of GUD are prevalent in Zulu men in Durban. Primary syphilis was the commonest and was invariably present in mixed infections. Donovanosis was under-reported and was associated with a long delay before presentation. In this population, genital ulcers other than superficial lesions should be treated with anti-syphilitic therapy and oral antibiotics effective against chancroid and donovanosis.